Dinamika Proses Pemekaran Daerah Cilacap Barat - Adi Arbi Susanto; Turtiantoro . (Journal of Politic and Government Studies, 2017)
AbstractOne of the interesting issues of the post-war collapse of the new orde in 1998 was the rise of area expansion that occur at the level of provincial and regency/city. The area expansion is regarded as customarily done with intent and purpose to become an instant solution to improve the walefare of the community in the area. It is currently conducted by the government of Cilacap with area expansion plan into two areas, namely Cilacap Regency and West of Cilacap Regency. But the fact up to now the expansion area of West Cilacap yet also realized.Research methods used in this study is a qualitative approach to techniques of collecting data through observation, interview and documents studies. Informants in this study are Government of Cilacap Regency, DPRD of Cilacap Regency, Province Government of Central Java, DPRD of Central Java, activist of the expansion of West Cilacap, as well as LPPM Unsoed Purwokerto.The results show that the discourse of expansion plan of West Cilacap by area, access to public services and development that have not been evenly distributed. The actors behind the proposed expansion West Cilacap of executive agencies, community organizations, and also the legislature. While the reason for the life span of the process of the expansion of Western support is because of Cilacap which is less solid, the problem of determining the location of the county seat, the attitude of the Governor of Central Java which has yet to give a respon to the proposed expansion, as well as the establishment of a moratorium on policy the new autonomous region (DOB) by the Central Government.The recommendations which could be awarded against the dynamics that occur in the process of the expansion of West Cilacap are need for a public discussion forum was held to bring together related perceptions and views the proposed expansion of West Cilacap. Every actors involved in the process of expansion of West Cilacap in order to assume the role more maximum. As for Mr. Ganjar Pranowo as Governor of Central Java, we recommend that you immediately may determine the attitude or at least give an explanation what actually is the reason up to now still haven't taken action related proposed expansion of West Cilacap.Keywords: West Cilacap, The Expansion Areas, The New Autonomous Region